The Use and Functions of Discourse Markers in EFL Classroom Interaction - Claudia Marcela Chapetón Castro (Profile: Issues in Teachers' Professional Development)
The aim of this paper is to investigate classroom interaction in the context of English as a foreign language being the teacher a nonnative speaker of the language. One specific aspect of classroom interaction and language use is the focus of attention, namely discourse markers (DMs). Using data from an EFL class, this study describes the occurrences and frequencies of DMs. It also provides an account for the main functions of DMs as they were used by a nonnative teacher of English and five adult students of EFL. A qualitative analysis reveals that discourse markers fulfill a number of textual and interpersonal functions which may contribute greatly to the coherent and pragmatic flow of the discourse generated in classroom interaction.